GeminiHeat wrote:
If \(r(r-4)=12\) where r represents a positive integer, then \((r-2)^2 +10= \)
A 18
B 26
C 36
D 40
E 52
\(r(r-4)=12\)
=> Product of 2 numbers at a gap of 4 is 12
=> The numbers are 6 and 2 or -2 and -6
\(=> r = 6 or -2\)
Alternate: \(r(r-4)=12\)
\(=> r^2 - 4r - 12 = 0\)
\(=> (r - 6)(r + 2) = 0\)
\(=> r = 6 or -2\)
Thus: \((r-2)^2 + 10 = \)
If \(r = 6: (r-2)^2 + 10 = 26\)
If \(r = -2: (r-2)^2 + 10 = 26\)
Answer BAlternate approach: \(r(r-4)=12\)
\(=> r^2 -4r = 12\)
\(=> r^2 -4r + 4 = 16\)
\(=> (r - 2)^2 = 16\)
\(=> (r - 2)^2 + 10 = 16 + 10 = 26\)
Answer B